PENGEMBANGAN MULTIMEDIA INTERAKTIF SUKU ADAT DAN TRADISI DI INDONESIA SEBAGAI MEDIA PEMBELAJARAN SISWA MTS NEGERI 1 BANYUMAS - Pandy Affan Daffar; Annisa Al Kautsar; Reza Irfan Wijaya; Syah Rafli Ramadhan (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2022)
Interactive multimedia is a learning media that represent information in form of animation that are interesting and easy to understand. Learning that talk about customs and traditions in Indonesia presented in a form of Interactive animation to build an interesting way in learning activities because of its various animation elements. In develpoing of this interactive media, researchers used Macromedia Flash 8 as animation software. This interactive multimedia learning model was made to make student at MTS Negeri 1 Banyumas more interested with the subject and retrive more information effectively. In this study, observation and questionnaire methods were used to determine the succes rate of learning activities using interactive multimedia for student at MTS Negeri 1 Banyumas.